PERANCANGAN ENTERPRISE COLLABORATION SYSTEM DENGAN KONSEP GAMIFIKASI - Minda Mora Purba (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2017)
System Collaboration Enterprise by using the concept of gamification, is a system used in an environment of an enterprise in which to apply the entire collaboration process functional therein by using the technique of game design, and place it into a game environment (gamespace), which aims to transform the work of each individual into a material game to be able to monitor and track the performance of each functional process and the perpetrator. Writing is created by studying the state of collaboration in an enterprise environment, both of the systems that support the activities of each functional area, the behavior of each actor system, as well as the technology used. Then try to build Enterprise Collaboration System using gamification concepts to improve retention, attention, and interactions between roles in a system in Enterprise.